Răspuns :
Răspuns:
=2√2-2+√6-√3
Explicație pas cu pas:
a(2-√3)+1/(2+√2)=√2/2
a(2-√3)+(2-√2)/2=√2/2
a(2-√3)+1=√2
a(2-√3)=√2-1
a=(√2-1)/(2-√3)= (√2-1)*(2+√3)=2√2-2+√6-√3 le scrii in ce ordine vrei
am tinut cont ca 1/(2-√3)=(2+√3)/(4-3)=2+√3
si ca 2²-(√2)²=4-2=2
[tex]a*(2-\sqrt{3})-\frac{1}{\sqrt{2}(\sqrt{2}+1) } =\frac{\sqrt{2} }{2}[/tex]
Rezolvare:
a×(2-√3) - 1/(2+√2) = √2/2 raționalizezi 1/(2+√2) cu 2-√2
a×(2-√3) - (2-√2)/(4-2) = √2/2
a×(2-√3) = √2/2 + (2-√2)/2
a×(2-√3) = 2/2
a = 1/(2-√3) raționalizezi cu 2+√3
a = (2+√3)/(4-3)
a = 2+√3